Identification of MYH9 Key Domain Involved in the Entry of PRRSV Into Permissive Cells - Li, Liangliang; Sun, Weiyao; Hu, Qifan; Wang, Tongtong; Zhu, Guang; Zhao, Qin; Zhou, En-Min (Frontiers in Microbiology, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) is an important pathogen that causes huge losses economically to the pig industry worldwide. Previous research suggested that receptor-dependence is necessary for PRRSV infection. MYH9 and CD163 are indispensable for PRRSV entry into a porcine alveolar macrophage. In the present study, human MYH9 (hMYH9) and mouse MYH9 (mMYH9), similar to swine MYH9, could also accelerate PRRSV infection in pCD163-mediated cell lines. Knockdown of MYH9 activity using the specific small interfering RNA or inhibitor (Blebbistatin) concomitantly decreased PRRSV infection. C-terminal fragment of MYH9 (PRA) proteins from different mammalian species contains a conserved binding domain (aa1676-1791) for PRRSV binding since the recombinant MYH91676-1791protein could inhibit the PRRSV infection significantly. Furthermore, the specific polyclonal antibody of MYH91676-1791 could block PRRSV infection in host cells. These data strongly supported that MYH9, a very important cofactor, participated in PRRSV entry into target cells, which may develop a new therapeutic agent to control PRRSV infection.